Attention and driving performance modulations due to anger state: Contribution of electroencephalographic data. (1st January 2017) - Techer, Franck; Jallais, Christophe; Corson, Yves; Moreau, Fabien; Ndiaye, Daniel; Piechnick, Bruno; Fort, Alexandra
Highlights: The influence of anger on attentional processing was observed during driving. Anger provoked a reduction of visual N1 peak amplitude. The standard deviation of lateral position was higher for angry drivers. Anger may combine the effects of a high arousal and mind-wandering episodes. Abstract: Driver internal state, including emotion, can have negative impacts on road safety. Studies have shown that an anger state can provoke aggressive behavior and impair driving performance. Apart from driving, anger can also influence attentional processing and increase the benefits taken from auditory alerts. However, to our knowledge, no prior event-related potentials study assesses this impact on attention during simulated driving. Therefore, the aim of this study was to investigate the impact of anger on attentional processing and its consequences on driving performance. For this purpose, 33 participants completed a simulated driving scenario once in an anger state and once during a control session. Results indicated that anger impacted driving performance and attention, provoking an increase in lateral variations while reducing the amplitude of the visual N1 peak. The observed effects were discussed as a result of high arousal and mind-wandering associated with anger. This kind of physiological data may be used to monitor a driver's internal state and provide specific assistance corresponding to their current needs.